Doing Research‐Creation in School: Keeping an Eye on the Ball. (5th August 2021) - Pahl, Kate; Pool, Steve
Abstract: This article explores the potential of the idea of 'research‐creation' when working with children making films in the context of a project that explored children's experience of school. The proposition of the article is that rather than see children's work as something to be discussed or extracted from, if it is seen as 'the work' it is differently situated. In the article, an artist and an ethnographer explore the potential of artistic methodologies in working collaboratively with children. The article describes this process and engages with an interdisciplinary lens to explore the nature of this kind of work. The results of the art‐making activities included a series of short films made by children on their experience of feeling odd in school. Within these films, ideas surfaced such as ghosts or day‐dreaming. In the conclusion the implications for artistic research with children are explored.